Polymer electrolytes based PAN for dye-sensitized solar cells - Jawad, Mohammed Kadhim (Iraqi Journal of Physics, 2019)
Solar cells has been assembly with electrolytes including I−/I−3 redox duality employ polyacrylonitrile (PAN), ethylene carbonate (EC), propylene carbonate (PC), with double iodide salts of tetrabutylammonium iodide (TBAI) and Lithium iodide (LiI) and iodine (I2) were thoughtful for enhancing the efficiency of the solar cells. The rendering of the solar cells has been examining by alteration the weight ratio of the salts in the electrolyte. The solar cell with electrolyte comprises (60% wt. TBAI/40% wt. LiI (+I2)) display elevated efficiency of 5.189% under 1000 W/m2 light intensity. While the solar cell with electrolyte comprises (60% wt. LiI/40% wt. TBAI (+I2)) display a lower efficiency of 3.189%. The conductivity raises with the raising TBAI salt weight ratio and attains the maximum value of 1.7×10−3 S. cm−1 at room temperature with 60% wt. TBAI, and the lower value of ionic conductivity of 5.27×10−4 S. cm−1 for electrolyte with 40% wt. TBAI. The results display that the conductivity rises with rising temperature. This may be attributed to the extending of the polymer and thereby output the free volume. The alteration in ionic conductivity with temperature obeys the Arrhenius type thermally activated process. The differences in activation energy mightily backup the alteration in the electrical conductivity.